ChemInform Abstract: Platinum N‐Heterocyclic Carbene Nanoparticles as New and Effective Catalysts for the Selective Hydrogenation of Nitroaromatics. Issue 30 (29th July 2014) - Lara, Patricia; Suarez, Andres; Colliere, Vincent; Philippot, Karine; Chaudret, Bruno
Abstract Functional groups such as hydroxy, benzyloxy, carbonyl, cyano, and halogens are tolerated under the present reaction conditions.